Heterosis for Fruit Yield and its Components in Brinjal (Solanum melongena L.) - Kuldeep Singh (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
An experiment was conducted with 14 parents and 40 F1s to study heterosis in brinjal. Crosses showing significant heterosis over the better parent were: HE12 X Aruna for first fruit set; BR-112 X Aruna for fruit length and diameter; Pant Samrat X Punjab Neelam for number of fruits per plant; H-7 X Aruna for fruit weight; H-9 X S-16 for total yield per plant; Negative heterosis were recorded in KT-4 X Aruna for borer and Pant in Rituraj X Punjab Neelam for nematode infestation.